Mengubah Sampah Menjadi Peluang Melalui Pemilahan Dan Pemanfaatan Sampah Di Kawasan Wisata Pantai Paradiso - Mooy, Dikky; Janri D. Manafe; Enos Kabu; Reysanti M. Djami; Plafianto J. Himpi; Rohani P. Dima; Surya S. Tarigan; Irience R.A. Manongga; Wilhelmina Muni; Supriyani, Supiyani; Caryn E. Mau; Aqnes P.P. Lobo (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract The community service activity that was carried out on November 23, 2024 was quite successful in attracting community participation and visitors to Paradiso Beach. The activity was packaged in the form of an interesting mini event, this activity successfully combined the transfer of waste sorting knowledge with entertainment. Not only sharing knowledge but also providing entertainment to the surrounding community with regional dances and modern dance as entertainment and preservation of local culture. This event was guided by a professional host to make it more interesting and presenting singers as performers. This event was opened directly by the Head of Oesapa Barat and attended by around 30 local residents and dozens of other visitors to Paradiso Beach. Keyword: Paradiso, Beach, Waste Abstrak Kegiatan pengabdian masyarakat yang telah dilaksanakan pada 23 November 2024 ini tergolong sukses dalam menarik partisipasi masyarakat dan pengunjung Pantai Paradiso. Kegiatan di kemas dalam bentuk mini event yang yang menarik, kegiatan ini berhasil menggabungkan transfer ilmu pemilahan sampah dengan hiburan. Tidak hanya membagikan ilmu tapi juga memberikan hiburan kepada masyarakat sekitar dengan tarian daerah dan modern dance sebagai hiburan dan pelestarian budaya lokal. Adapun acara ini dipandu oleh host professional agar semakin menarik dan menhadirkan penyanyi sebagai pengisi acara. Acara ini dibuka langsung oleh Lurah Oesapa Barat dan dihadiri sekitar 30 warga setempat dan puluhan pengunjung Pantai Paradiso lainnya. Kata Kunci: Paradiso, Pantai, Sampah